Upaya Meningkatkan Keterampilan Menulis Teks Eksplanasi melalui Strategi Menulis Terbimbing pada Mata Pelajaran Bahasa Indonesia di Kelas VC Min 1 Kota Mataram Tahun Pelajaran 2025/2026 - M. Ikbal Fahrurrozi; Hilmiati; Akmaluddin (Mataram University, 2026)
This study aimed to improve students’ explanatory text writing skills through the implementation of a guided writing strategy in the Indonesian language subject for Class VC students at MIN 1 Mataram City in the 2025/2026 academic year. This study employed Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, evaluation, and reflection. The research subjects were 37 students. Data were collected through written tests, observations of students’ activities, and documentation. The data were analyzed using descriptive qualitative and quantitative methods. The results showed that the implementation of the guided writing strategy improved students’ explanatory text writing skills. In Cycle I, the students’ mean score was 76.7, with a classical mastery level of 70%, consisting of 26 students who achieved mastery and 11 students who had not yet achieved mastery. In Cycle II, the mean score increased to 86.6, with a classical mastery level of 92%, consisting of 34 students who achieved mastery and 3 students who had not yet achieved mastery. Students’ activities also improved from the moderately active category in Cycle I to the very active category in Cycle II. Based on these findings, it can be concluded that the guided writing strategy can improve the explanatory text writing skills of Class VC students at MIN 1 Mataram City and achieve the predetermined success indicators.